Excessive and Problematic Internet Use During the Coronavirus Disease 2019 School Closure: Comparison Between Japanese Youth With and Without Autism Spectrum Disorder - Kawabe, Kentaro; Hosokawa, Rie; Nakachi, Kiwamu; Yoshino, Ayumi; Horiuchi, Fumie; Ueno, Shu-ichi (Frontiers in Public Health, 2020)
Internet use in the youth has increased manifold during the coronavirus disease 2019 (COVID-19) pandemic. Individuals with autism spectrum disorder (ASD) generally have a higher risk of problematic internet use. The aim of this study is to investigate the differences in internet and related digital media use between children with ASD and their typically developing counterparts during the COVID-19 pandemic. In this online survey in Japan conducted from April 30 to May 8, 2020. We analyzed data of 84 children with ASD and 361 age- and gender-matched controls duration before and after school closure. Digital media use duration was significantly longer in the ASD group than in the control group before the pandemic. There was a significant increase in both groups after school closure although there were no differences between the groups. Using a multivariate model with the time change, there were significant correlations between gender, school level, and the presence or absence of ASD. There was a significant change in internet use in children after school closure. It is necessary to establish strategies to prevent excessive internet use in school children in the post-pandemic world.